LAW AND SOCIAL AFFAIRS; AN ANALYSIS OF EARLY MARRIAGE FACTORS IN NIBUNG VILLAGE, KOBA DISTRICT, CENTRA BANGKA REGENCY - Gunawan, Arifin Faqih (Berumpun: International Journal of Social, Politics and Humanities, 2019)
The Marriage Law, number 1 of 1974 gives the minimum age limit for a person to be allowed to marry if a man has reached the age of 19 years and a woman has reached the age of 16 years. This study explains the factors influence the occurrence of early marriage in Nibung Village, Koba District, Central Bangka Regency. The purpose of this study is to identify the  factors that influence the occurrence of early marriage in Nibung Village, and to see the public's understanding of early marriage from the side of the Law. The results of this study indicate that there are 2 categories of factors that influence early marriage. There are two positive trend factors which are parents’ perceptions & culture and beliefs. There are also two negative trend factors which are intellectuality and the value of virginity